2015
DOI: 10.1021/acs.jchemed.5b00592
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effectiveness of a Semi-Self-Paced Flipped Learning Format in a College General Chemistry Sequence

Abstract: Flipped learning has come to the forefront in education. It maximizes learning by moving content delivery online, where learning can be self-paced, allowing for class time to focus on student-centered active learning. This five-year cross-sectional study assessed student performance in a college general chemistry for majors sequence taught by a single instructor, comparing the flipped learning format to a more traditional lecture format. Students’ conceptual knowledge was captured through the use of American C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 30 publications
2
90
2
5
Order By: Relevance
“…Relatively weaker students were also found to benefit more than their stronger peers in terms of outcomes on tests in a flipped organic chemistry context (Fautch, 2015). On the other hand, our results offer a counterpoint to most other reports on college learning, which show a general trend of superior performance by students in flipped, inquiry-based, and/or other types of cooperative learning classroom environments (Freeman et al, 2014;Weaver and Sturtevant, 2015;Hibbard et al, 2016;Warfa, 2016). As an illustration, two recent studies specifically in organic chemistry revealed test performance benefits for learners in student-centered, active-learning organic chemistry classrooms (Hein, 2012;Conway, 2014).…”
Section: Classroom Format and Content Knowledgecontrasting
confidence: 76%
“…Relatively weaker students were also found to benefit more than their stronger peers in terms of outcomes on tests in a flipped organic chemistry context (Fautch, 2015). On the other hand, our results offer a counterpoint to most other reports on college learning, which show a general trend of superior performance by students in flipped, inquiry-based, and/or other types of cooperative learning classroom environments (Freeman et al, 2014;Weaver and Sturtevant, 2015;Hibbard et al, 2016;Warfa, 2016). As an illustration, two recent studies specifically in organic chemistry revealed test performance benefits for learners in student-centered, active-learning organic chemistry classrooms (Hein, 2012;Conway, 2014).…”
Section: Classroom Format and Content Knowledgecontrasting
confidence: 76%
“…Finally, as some recent studies have looked at how student-centred learning and the individualised learning opportunities offered by the support of the flipped classroom can have an impact on the efficacy of the flipped-learning design in raising students' attainment and increasing their engagement, an empirical and longitudinal study to explore this notion would be beneficial (e.g. Hibbard et al, 2016;O'Flaherty and Phillips, 2015;Little, 2015).…”
Section: Conclusion and Looking Aheadmentioning
confidence: 99%
“…Alanyazın incelendiğinde, TES modelinin matematikten (DeSantis, Van Curen, Putsch ve Metzger, 2015), kimya öğretimine (Schultz, Duffield, Rasmussen ve Wageman, 2014;Trogden, 2015) dil öğretiminden (Başal, 2015, Helgeson, 2015 fizik öğretimine (Kettle, 2013) kadar birçok ders de çalışıldığı anlaşılmaktadır. İlgili çalışmalar, TES modelinin pratiğinden (Hibbard, Sung ve Wells, 2016;MacKinnon, 2015;Maxson ve Szanislo, 2015;Pearson, 2013;Prashar, 2015;Sharma, Lau, Doherty ve Harbutt, 2015;Smith, 2013), teorisine (Filiz ve Kurt, 2015;Karadeniz;Mehring, 2016;Nederveld & Berge, 2015;Seery, 2016;Temizyürek ve Ünlü, 2015) geniş bir alana yayıldığı söylenebilir.…”
Section: İlgili Alanyazın Taramasıunclassified
“…Elde edilen bulgular Tablo 6'da gösterilmiştir. (Davies, Dean ve Ball, 2013;Hibbard, Sung ve Wells, 2016;MacKinnon, 2015;Pearson, 2013;Prashar, 2015;Tune, Sturek ve Basile, 2013;Wilson, 2013 Marlowe, 2012;Saunders, 2014) yer almaktadır. Nitekim, TES modeli internete ulaşım sorunları, öğrencilerin gereken hazırlıkları yapmadan sınıfa gelmeleri, bazı öğrencilerin yeni uygulamalara ilişkin dirençleri (McCarthy, 2016), anında dönüt alınmaması (Ramirez, Hinojosa ve Rodriguez, 2014) gibi açılarından ise dezavantajlı olduğu belirtilmektedir.…”
Section: Tablo 5 öğRetmen Adaylarının üStbiliş Farkındalık öNtest Puunclassified